Development of Harmaline-induced Tremor in a Swine Model. (13th March 2018) - Lee, Jihyun; Kim, Inyong; Lee, Jeyeon; Knight, Emily; Cheng, Lei; Kang, Shin il; Jang, Dong Pyo; Chang, Su-Youne
Background: In the field of translational neuroscience research, it is critical to utilize a large animal model to test the feasibility, safety, and functionality of novel therapies. Here, we describe a protocol for the development of a large animal model of tremor. Methods: In a pig model, tremor was induced with harmaline and measured with wireless accelerometers attached to the limbs. Three different doses of harmaline were tested and three repetitive injections were made at 72-hour intervals. To fully characterize the drug-induced tremor, onset time, tremor amplitude, maintained duration, and peak tremor frequency were analyzed. Results: Harmaline-induced tremor appeared immediately following intravenous injection of harmaline. Tremor was maintained over 2 hours. Its frequency was 10–16 Hz, which was independent of doses. Dose-dependent responses were observed in tremor amplitude, triggering time, and tremor-maintained duration. Repetitive injection of harmaline desensitized the harmaline effect. Discussion: We provide a detailed protocol for training, drug injection, device selection, and tremor recording optimized to create a swine model of tremor with harmaline. Our protocol provides reliable tremor in pigs and suggests pig as a valid translational large animal model of tremor.